تأثير طريقة التّقليد والتّحفيظ باستخدام البطاقة الذّكيّة في فهم المفردات العربيّة لدى طلاب مدرسة أندلوسيا الابتدائيّة الإسلاميّة تابان - Pil Hayati; Arman Husni; Yelfi Dewi S; Eka Rizal (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The researcher found problems in understanding vocabulary among fourth-grade students at Andalusia Islamic Primary School in Tapan. There are many educational methods and means that can be creative, including the game. There are no attractive educational methods in teaching vocabulary. Students think that the Arabic language is difficult, boring, and less interesting. Objectives of this scientific thesis: 1) Determine the effect of the method of imitation and memorization using the smart card on understanding Arabic vocabulary among students in the fourth semester of Andalusia Islamic Primary School, Taban. 2) To determine the extent of the effect of the method of imitation and memorization using a smart card on understanding vocabulary among students at Andalusia Taban Primary School. In this study, the researcher used multiple choice pre-test and post-test data collection. Asymp.Sig. (2-tailed) 000 < 0.05. From the data obtained, it can be concluded that the research hypothesis is acceptable, meaning that there is a significant impact on the effect of the method of imitation and memorization using the smart card on understanding Arabic vocabulary among the students of Andalusia Islamic Primary School, Tapan.